Characterizing the therapeutic response to deep brain stimulation for treatment-resistant depression: a single center long-term perspective - Crowell, Andrea L.; Garlow, Steven J.; Riva-Posse, Patricio; Mayberg, Helen S. (Frontiers in Integrative Neuroscience, 2015)
The number of depressed patients treated with deep brain stimulation (DBS) is relatively small. However, experience with this intervention now spans more than 10 years at some centers, with study subjects typically monitored closely. Here we describe one center’s evolving impressions regarding optimal patient selection for DBS of the subcallosal cingulate (SCC) as well as observations of short- and long-term patterns in antidepressant response and mood reactivity. A consistent time course of therapeutic response with distinct behavioral phases is observed. Early phases are characterized by changes in mood reactivity and a transient and predictable worsening in self ratings prior to stabilization of response. It is hypothesized that this characteristic recovery curve reflects the timeline of neuroplasticity in response to DBS. Further investigation of these emerging predictable psychiatric, biological, and psychosocial patterns will both improve treatment optimization and enhance understanding and recognition of meaningful DBS antidepressant effects.